Effect of Adding Basil Leaf Extract (Ocimum basilicum) on Reducing Ag+ Ions to Ag0 by Colorimetry: Pengaruh Penambahan Ekstrak Daun Kemangi (Ocimum basilicum) Terhadap Reduktor Ion Ag+ menjadi Ag0 secara Kolorimetri - Ambarita, Petrus Alvin Peter Ambarita; Nurhayati, Veni Putri; Rani, Fella Anindya; Putri, Tia Azzahra; Khansa, Shefia Dhiya; Gultom, Rifka; Rorensya, Chika Ari Dinar; Saputra, Iwan Syahjoko (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2024)
Nanotechnology has become a significant focus of research in efforts to address various challenges across multiple fields, including the synthesis of metal nanoparticles using natural bioreductors. This study explores the use of basil leaves (Ocimum basilicum) as a natural bioreductor for the synthesis of silver nanoparticles (Ag). The extract from basil leaves is rich in flavonoids, which serve as reducing agents in the green synthesis process of silver nanoparticles. The research methods include the preparation of basil leaves, extraction of simplicia, phytochemical analysis, and testing the bioreduction of Ag+ ions. The results indicate that the addition of basil leaf extract effectively reduces Ag+ ions to Ag⁰, marked by a color change in the solution to yellow-green within 60 minutes. The uniqueness of this study lies in utilizing basil leaves as an environmentally friendly bioreductor in the synthesis of silver nanoparticles. These findings have broad potential applications in catalysis, sensing technologies, and cosmetics.